2014
DOI: 10.1002/nbm.3097
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metabolites in infiltrating gliomas using ex vivo 1 H high‐resolution magic angle spinning spectroscopy

Abstract: Gliomas are routinely graded according to histopathologic criteria established by the World Health Organization (WHO). Although this classification can be used to understand some of the variance in the clinical outcome of patients, there is still substantial heterogeneity within and between lesions of the same grade. This study evaluated image-guided tissue samples acquired from a large cohort of patients presenting with either new or recurrent gliomas of grades II-IV using ex vivo proton high-resolution magic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 50 publications
5
50
0
1
Order By: Relevance
“…An increased total choline (tCho) signal, which consists of signals from phosphocholine (PC), glycerophosphocholine (GPC), and free choline (Cho), and whose chemical structures are shown in Figure 1, has been detected by 1 H MRS in all cancers tested so far (7). High-resolution 1 H MRS, which can resolve the signals from the individual components of the tCho signal, confirmed the increase of PC in breast (812), prostate (13, 14), ovarian (15), endometrial (16), cervical (15), and brain cancers (1719). In some cancer cell types such as isolated breast and ovarian cancer cells, a relative decrease of GPC was observed as well, which led to the suggestion to use a higher ratio of PC/GPC as a marker of tumor progression (20, 21).…”
Section: Introductionmentioning
confidence: 77%
“…An increased total choline (tCho) signal, which consists of signals from phosphocholine (PC), glycerophosphocholine (GPC), and free choline (Cho), and whose chemical structures are shown in Figure 1, has been detected by 1 H MRS in all cancers tested so far (7). High-resolution 1 H MRS, which can resolve the signals from the individual components of the tCho signal, confirmed the increase of PC in breast (812), prostate (13, 14), ovarian (15), endometrial (16), cervical (15), and brain cancers (1719). In some cancer cell types such as isolated breast and ovarian cancer cells, a relative decrease of GPC was observed as well, which led to the suggestion to use a higher ratio of PC/GPC as a marker of tumor progression (20, 21).…”
Section: Introductionmentioning
confidence: 77%
“…However, although they provide crucial information on the structure and perfusion of the tumor as well as the integrity of the blood-brain barrier (BBB), these methods do not provide metabolic information on the lesions. 1 H magnetic resonance spectroscopy (MRS) in vivo or in biopsy samples allows probing steady-state metabolite levels, and several studies have demonstrated the potential of 1 H MRS to differentiate tumors from normal brain and non-neoplastic lesions 13,1519 . Tumors are usually associated with high levels of choline-containing metabolites (comprised of choline, phosphocholine (PC) and glycerophosphocholine (GPC)) and low levels of N-acetyl-aspartate as well as an increase in lactate level in high-grade tumors 13,17 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, metabolomics has been increasingly pursued in relation to cancer, either entailing the analysis of tumor tissue (e.g. melanoma5, breast67, ovarian8, colorectal9, brain101112) or of biofluids. The use of biofluid metabolomics in cancer research has consistently increased13, minimally invasive samples (plasma/serum and urine) having been used to study ovarian1415, colorectal16, kidney171819, breast1520, lung2122 and liver232425 cancers, either using Nuclear Magnetic Resonance (NMR) spectroscopy or Mass Spectrometry (MS).…”
mentioning
confidence: 99%